2018
DOI: 10.1111/nmo.13509
|View full text |Cite
|
Sign up to set email alerts
|

Multiple psychological factors predict abdominal pain severity in children with irritable bowel syndrome

Abstract: Background Anxiety and depression are implicated as contributors to abdominal pain in pediatric irritable bowel syndrome (IBS) but is unclear if this pain is associated with other psychological factors. The study objective was to test if the impact of anxiety or depression on IBS symptom severity is mediated by somatization and/or pain catastrophizing. Methods We utilized baseline data from local pediatric IBS clinical studies. Through mediation analysis, we assessed whether somatization or pain catastrophizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 63 publications
4
39
0
3
Order By: Relevance
“…We note that our research examined whether child anxiety accounts for caregiver distress in relation to pain-related outcomes, which we conceptualized to include somatization (consistent with other literature). However, we note that yet other research has explored somatization as a mediator between child anxiety and pain severity [45,46], and between coping with pain and pain severity [45]. We did not explicitly examine coping with pain in our investigation.…”
Section: Future Research and Limitationsmentioning
confidence: 99%
“…We note that our research examined whether child anxiety accounts for caregiver distress in relation to pain-related outcomes, which we conceptualized to include somatization (consistent with other literature). However, we note that yet other research has explored somatization as a mediator between child anxiety and pain severity [45,46], and between coping with pain and pain severity [45]. We did not explicitly examine coping with pain in our investigation.…”
Section: Future Research and Limitationsmentioning
confidence: 99%
“…Indeed, several studies found that specific pain-related cognitions and coping behaviours are directly related to pain and disability. For example, one study 110 found that the effect of anxiety and depression on abdominal pain was mediated by somatization and pain catastrophizing. Studies on the active ingredients of CBT also found that treatment effects on disability and pain can be predicted by changes in pain-related cognitions such as catastrophizing, disease threat and avoidance behaviours 111,112 .…”
Section: Psychological Factorsmentioning
confidence: 99%
“…The SSD and the functional GI diseases mostly coexist [ 12 ], ranging from 15 to 48% in IBS patients [ 13 , 14 ]. This evidence is of particular interest considering the close relationship between pain and somatization in patients with functional diseases [ 15 ], including those with IBS [ 16 ].…”
Section: Introductionmentioning
confidence: 99%